Geographic Distribution of Foreign Medical Graduates in US Neurosurgery Training Programs from 2007 to 2017. (16th November 2020) - Chandra, Ankush; Brandel, Michael G; Wadhwa, Harsh; Pereira, Matheus P; Lewis, Cole T; Haddad, Yazeed; Lu, Victor M; Almeida, Neil; Nuru, Mohammed; Spatz, Jordan; Aghi, Manish K
Abstract: INTRODUCTION: Foreign medical graduates (FMGs) have been part of the US physician workforce for several decades. However, the increasing competitiveness of the neurosurgery residency match has made it progressively challenging for FMGs to match. METHODS: Retrospective review of American Association of Neurological Surgeons membership data (2007-2017). Scopus was used to collect bibliometrics at the beginning of residency. RESULTS: From 2, 009 neurosurgical residents, 165 (8.2%) were FMGs, of which most were male (n = 148; 89.6%) with a median age of 34.0 years. Top five feeder countries were India (13.9%; n = 23), Lebanon and Pakistan (9.1%; n = 15), Caribbean Region (7.2%; n = 12), Mexico (6.67%; n = 11), and Greece (3.6%; n = 6). Compared to FMGs from non-top feeder countries, top feeder FMGs had higher H-indices (2 vs 4, P = . 049) and greater number of publications (2 vs 5, P = . 04), were more likely to have an MBBS/MBBCh (n = 38 vs n = 17, P = . 03). While both cohorts had similar frequencies of being affiliated to a US neurosurgery program prior to the match (non-top feeder = 33 vs top feeder = 38, P = . 9), FMGs from non-top feeder countries were almost three-times more likely to match at an affiliated program (8 vs top-feeder = 3, P = . 03), while FMGs from top-feeder countries were 1.5-times more likely to match at an NIH Top-40 program (33 vs non-top feeder = 21, P = . 03). Although the number of schools from which FMGs emerged was similar between top-feeder versus non-top-feed countries, top-feeder FMGs (n = 43 versus non-top feeder = 20, P < . 001) had twice as many candidates from major feeder medical schools successfully matching into a US neurosurgery program. CONCLUSION: FMGs have diverse geographic origins with certain countries and medical schools having a greater share of graduates matching into US neurosurgical programs. Graduates from top-feeder countries have higher bibliometrics, more frequently come from major feeder schools and have greater match success at a broader selection of programs and NIH top 40 programs. Future studies characterizing FMG country and medical school origins may enable foreign students to target particular schools or countries to study in and could allow US programs to better evaluate the training environments that FMGs originate from.